Participação da glia hipotalâmica na modulação das respostas neuroendócrinas, comportamentais e cardio-respiratórias induzidas pela angiotensina II no ventrículo lateral de ratos não anestesiados - Flôr, Atalia Ferreira de Lima (2016)
The central Ang II (ANG II) induces neuroendocrine, behavioral and cardiovascular responses. Knowing that AT1 and AT2 receptors for ANG II are located in neurons and glial cells in the lamina terminalis (LT), our hypothesis is that neuroendocrine, behavioral and cardiorespiratory responses induced by central ANG II are mediated by glia of lamina terminalis. Our aim was to evaluate the participation of the glia of lamina terminalis in the release of plasma vasopressin (AVP) and oxytocin (OT), water and sodium (1.5%) intake and cardiorespiratory responses induced by ANG II into lateral ventricle (LV). We used Wistar rats [(260-280g) Ceua/Cbiotec 133/2015]. We perform microinjections of ANG II diluted in sterile saline solution (0.9% saline) with final concentration of 25 ou 50 ng/0.5 μl and of Fluorocitrate [(FCt) inhibitor of glial activity] with final concentration of 21 ou 41 μg/0.5 μl or sterile saline 0.9% (500nl) into VL of the unanesthetized rats. Plasma was collected for analysis of AVP and OT concentration by radioimmunoassay. The analysis of the water and sodium (1.5%) intake were done after adaptation of animals to the metabolic cage. In another group of animals, the femoral artery was catheterizedfor the records of baseline blood pressure (BP, mmHg) and heart rate (HR, bpm). For the record the respiratory rate (cpm) the animals were placed in a plethysmographic chamber. The results showed that ANG II into VL promoted an increase in the AVP [2.3 ± 0.4 vs. 1.3 ± 0.1 pg/ml, p=0.039 (n=6)] and OT [3.9 ± 0.8 vs. 1.4 ± 0.2 pg/ml, p=0.025 (n=6)] compared to the control saline (0.9%). FCt into VL increased plasma OT (2.6 ± 0.4 vs. 1.4 ± 0.2 pg/ml, p=0.024 (n=6)], but did not change the plasma AVP (0.99 ± 0.1 vs. 1.3 ± 0.1 pg/ml, p=0.78 (n=6)]. Prior microinjection of FCt attenuated ANG II-induced AVP (1.3 ± 0.2 vs 2.3 ± 0.4 pg/ml, p=0.05 (n=6)], but no OT (2.9 ± 0.4 vs. 3.9 ± 0.8 pg/ml, p=0.31 (n=5-6).] The plasma release ANG II increased the cumulative water (5.3 ± 1.6 vs. 1.2 ± 0,4 ml/4 h, p=0.02 (n=4-6)] and sodium (1.5 %) intake [16 ± 1.1 vs. 2.5 ± 0.7 ml/4 h, p=0.0001 (n=5-6)]. The FCt did not change the cumulative water [1.3 ± 0.3 vs. 1.2 ± 0.4 ml/4 h, p=0.79 (n=5-6)], but decreased sodium (1.5 %) intake [0.83 ± 0.3 vs. 2.5 ± 0.7 ml/4 h, p=0.04 (n=6)]. Prior microinjection of FCt decrease the sodium intake [2.7 ± 0.3 vs. 16 ± 1.1 ml/4 h, p=0.0001 (n=5-7)], but did not change the water intake induced by ANG II [8 ± 2.4 vs. 5.3 ± 1.6 ml/4 h, p=0.44 (n=4-7)]. ANG II into VL promoted increase in baseline MAP [137.8 ± 4.9 vs. 115.1 ± 3.5 mmHg, p=0.002 (n=7)]. The pressor response promoted by ANG II was significantly reduced after 5 minutes by prior microinjection of FCt [Δ12.6 ± 2.1 vs. Δ22.6 ± 1.9 mmHg, p=0.004 (n=7)]. Did not change by ANG II [311.7 ± 37.9 vs. 352.4 ± 15 bpm, p=0.10 (n=7)] or FCt [310.4 ± 16.7 vs. 341.3 ± 14 bpm, p=0.18 (n=7)] in HR (bpm) baseline. The ANG II did not changes in respiratory rate (FR) [109.6 ± 5.9 vs. 105.9 ± 4.6 cpm, p=0.63 (n=6)], tidal volume (VC) [8.6 ± 0.7 vs. 7.8 ± 0.7 mL.Kg-1, p=0.43 (n=6)] or expiratory volume in the first minute (VM) [950.7 ± 98.2 vs. 873.5 ± 86.7 mL.Kg-1.min-1, p=0.57 (n=6)]. The microinjection of FCt promoted significant decrease in basal FR [77.7 ± 3.8 vs. 105.9 ± 4.6 cpm, p=0.002 (n=6)], but did not change in VC [9.7 ± 0.6 vs. 7.8 ± 0.7 mL.Kg-1, p=0.66 (n=6)] and VC [827.2 ± 57.3 vs. 873.5 ± 86.7 mL.Kg- 1.min-1, p=0.66 (n=6)]. Our results suggest that the hypothalamic glial cells: 1) participate of plasma OT release and sodium intake; 2) modulate ANG II-induced AVP plasma release, sodium intake and pressor response; 3) furthermore, modulate the basal respiratory rate in unanesthetized rats.